Analisa perhitungan dan pemotongan PPh pasal 21 terhadap peraturan pemerintahan NO. 58 Tahun 2023 - Putri, Nessa Pavetria; Kirana, Nanda Wahyu Indah (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2024)
Taxes are mandatory monetary payments due to the government from all citizens; these funds serve both the public and the government. When businesses and people get money, they are subject to a tax called income tax. PPh Article 21 imposes a tax on any remuneration received by domestic individual taxpayers in relation to their employment, whether in the form of salary, wages, honorarium, allowances, or any other name or form. Article 21 of Government Regulation Number 58, which deals with Tax Rate Cuts, and its derivative laws, especially Minister of Finance Regulation Number 168 of 2023, lay forth the notion of relaxation with respect to income related to work, services, and activities of individual taxpayers. Our study's overarching goal is to ascertain whether or not PT. ABC's income tax filings, calculations, and applications comply with the requirements of Taxation Law no. 58 of 2023. The data analysis technique used is the descriptive analysis approach, which is a means of talking about issues that gives details about a scenario or data and how to apply that description to form conclusions about how to solve current problems. Article 21 of Law No. 58 of 2023 and the processes outlined in the Indonesian Tax Regulations are followed when determining how to calculate, withhold, and submit income tax. In accordance with the company's monthly arrangement, each employee receives their compensation straight at the start of each month.